RELATIONSHIP OF AUTHORITY OF VILLAGE HEAD WITH VILLAGE CONSULTATIVE BODY IN VILLAGE REGULATION ESTABLISHMENT - M Tasbir Rais (Indonesia Prime, 2020)
Village regulation is a statutory regulation set by the Village Head after being discussed and agreed together with the Village Consultative Agency. Perrule desa applies in the local village area in the Unitary State of the Republic of Indonesia which is intended as a further description of the higher legislation taking into account the social and cultural conditions of the local villagers. In the establishment of perrule desa,it should not be contrary tothe public interest and/or higher legislation. Therefore, masyarakat has the right to give input orally or in writing in order to prepare or discuss the draft village regulations before it is determined as village regulations. Based on the results of the research shows that the authority relationship between Kepala Desa as a village executive institution with Band Permusyawaratan Desa as the village legislature is domiciled equally asa partner without any subordinates under it. In this context, it can be said that Kepala Desa has an important role in its position asa long-hand state thatis close to the community and as a communityleader,as well asBand Permusyawaratan Desa has an important function in preparing village government policy with KepalaDesa.